Encyclopedia of Life Sciences 2011
DOI: 10.1002/9780470015902.a0023177
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositides – The Seven Species: Conversion and Cellular Roles

Abstract: Phosphoinositides are phospholipids that contain a phosphorylated inositol head group. The position and number of phosphate groups varies, which results in seven phosphoinositide species. A large family of enzymes have evolved to specifically modify phosphoinositides. Phosphoinositide kinases and phosphatases modify the phosphorylation state of the inositol head group, whereas phospholipases hydrolyse phosphoinositides to release the soluble head group in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Surprisingly, NCT-504 also robustly increased PI(3,5)P2 levels, and to a lesser extent increased levels of PI3P ( Figure 2B and E ). We did not observe an effect on PI(4,5)P2 levels ( Figure 2F ), which is consistent with other reports indicating that the cellular levels of this lipid are mostly generated from PI4P via type I PI4P 5-kinases ( Lietha, 2011 ). Kinetic measurement of PI levels showed that NCT-504 causes an increase in PI5P, PI(3,5)P2 and PI3P levels along with a decrease in PI4P, progressively over 12 hr ( Figure 2—figure supplement 2 ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Surprisingly, NCT-504 also robustly increased PI(3,5)P2 levels, and to a lesser extent increased levels of PI3P ( Figure 2B and E ). We did not observe an effect on PI(4,5)P2 levels ( Figure 2F ), which is consistent with other reports indicating that the cellular levels of this lipid are mostly generated from PI4P via type I PI4P 5-kinases ( Lietha, 2011 ). Kinetic measurement of PI levels showed that NCT-504 causes an increase in PI5P, PI(3,5)P2 and PI3P levels along with a decrease in PI4P, progressively over 12 hr ( Figure 2—figure supplement 2 ).…”
Section: Resultssupporting
confidence: 93%
“…Note that other PI levels were not tested in the dPI4PK Drosophila mutant. We hypothesized that elevation of PI5P might further impact the equilibrium between various PI species ( Lietha, 2011 ; Emerling et al, 2014 ; Balla, 2013 ). To test this hypothesis, we exposed wild type mouse embryonic fibroblasts to nontoxic concentrations of NCT-504 (10 μM) for 12 hr, and then evaluated the levels of PI by HPLC ( Figure 2 ; toxicity assay in Figure 2—figure supplement 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Receptor 13 is a useful tool for exploring PIP 2 -dependent cellular processes, many of which are linked to diseases including cancer [74], diabetes [14] and Lowe syndrome [45]. This work has identified PIP 2 as a potential drug target in the diagnosis and treatment of these disorders.…”
Section: Molecular Recognition Of Phosphatidylinositol Bisphosphate Wmentioning
confidence: 99%
“…These lipids recruit a unique set of effector proteins, which have PI recognition domains. Upon binding, the effector proteins are either guided to the appropriate location inside the cell or their activity is being modulated (Lietha, 2011).…”
Section: Phosphoinositides: Important Spatio-temporal Regulators Of Cell Signaling and Intracellular Traffickingmentioning
confidence: 99%